Abrogation of lung inflammation in sensitized Stat6-deficient mice is dependent on the allergen inhalation procedure - Trifilieff, Alexandre (2000)
1. Conflicting results have been reported about the role of Stat6 in allergen-induced airway inflammation. We have studied the influence of the allergen inhalation procedure on the inflammatory response using wild-type and Stat6-deficient mice generated on a C57BL/6 background. 2. Animals were immunized i.p. on day 0 and 7 with ovalbumin (OVA) and then received aerosolized OVA or phosphate buffer saline challenge (acute on day 14; chronic on day 14, 15, 16, 17 and 18) before being sacrificed at different time points. 3. Following an acute challenge, Stat6-deficiency fully abrogated the increase in serum IgE levels and the development of lung inflammation (inflammatory cell infiltration, IL-4 and IL-5 release, and increase in plasma leakage). 4. Following chronic challenge, despite the absence of IgE, IL-4 and IL-5, Stat6-deficient mice develop a characteristic lung inflammation, although the intensity was smaller when compared with the wild-type mice. 5. OVA-induced early bronchoconstriction was observed in wild-type mice only after chronic challenge, and this was totally abrogated in the Stat6-deficient animals. 6. These results suggest that Stat6 signalling is essential for the development of allergic airway inflammation following an acute allergen exposure. However, in a more chronic situation, the airway inflammatory response seems to be only partially mediated by Stat6.